Role of Intraoperative Ultrasonography on Neocortical Brain Tumor Surgery - Arifi, Muhamad Thohar; Bakhtiar, Yuriz; Andar, Erie; Priambada, Dody; Kurnia, Happy; Risdianto, Ajid; Tsaniadi, Krisna; Kusnarto, Gunadi; Setiyawan, Aris; Bunyamin, Jacob; et al. (Bangladesh Journal of Medical Science, 2020)
Objective: Among imaging modalities, ultrasonography (US) is one of the most versatilechoice, with its low cost, lack of radiation exposure, and minimally disrupted surgery flow.We described the use and characteristics of intraoperative ultrasonography (US) in selectedcases in our center to assist the intracranial tumor resection. Methods :Seventy patients wereoperated from 2011 to 2018 at Kariadi Hospital with the help of intraoperative US. Fifty sixpercents of cases were cystic tumors, 25% were abscess and 19% were metastatic tumors Weused seven parameters to measure the utility of intraoperative US and a utility score was devised(0 minimum, 7 maximum). Results: The utility score for intraoperative US was 7 in 3 cases(4%), 6 in 28 cases (54%), 5 in 21 cases (31%), 4 in 8 cases (11%), while no case had score ≤3. Conclusion: Intraoperative US is not only helpful in localizing lesions but also it can be usedin determining the morphology of the lesion for some cases, which was glioma in our case.Intraoperative US is also helpful when to start planning the site of entry and complete resection. Bangladesh Journal of Medical Science Vol.19(3) 2020 p.575-578